Ralph Erskine, (Skiing) Architect - McGowan, Jérémie Michael (Nordlit, 2008)
In this paper I focus on Ralph Erskine's enduring image in architectural discourse as the Arctic Architect of Modernism. My interest lies with the relationship between portrayals of Erskine - both in textual accounts an  images - and the way his sub-Arctic projects, especially his unrealised utopian projects for an ‘Ideal Town' north of the Arctic Circle, have been canonised in architectural discourse as exemplars of an architecture that is truly regional in character and, moreover, ideally suited to the unique cultural - especially with regard to indigenous populations - and environmental habitats of Arctic and sub-Arctic environments.
Keywords: Ralph Erskine; Arctic architecture